If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f + -1(2) = 0 Multiply -1 * 2 f + -2 = 0 Reorder the terms: -2 + f = 0 Solving -2 + f = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + f = 0 + 2 Combine like terms: -2 + 2 = 0 0 + f = 0 + 2 f = 0 + 2 Combine like terms: 0 + 2 = 2 f = 2 Simplifying f = 2
| 5-(8-x)=3-(x-6) | | -(v-2)=-4(v-8)-8v | | x(x+3)=-8 | | (2x^2)+5x+8=0 | | 16z=-128 | | 7-q-q-2q=80 | | 4p-25=-32+5p | | 4p-12=-3+p | | -7x-10x=-85 | | 4x-10x=70 | | -5x-15=-95 | | -60=3+9x | | (3x^2)-5x-7=0 | | (2x^2)+8x=0 | | 1+x^2=0 | | (2x^2)-7x-1=0 | | 27a^3x^4-8x=0 | | 8+2x=x+40 | | 3y+24+6-2=33 | | -28+4=0 | | ln(x+1)ln(x)+ln(x^2)=1 | | ln(x+a)ln(x)+ln(x^2)=1 | | 53-2x=5x | | 11x-10=54 | | 6p^2+25-119=0 | | (6a^3+6a^2-7)+(5a^3-6a+8)= | | 2x^2-45=0 | | y+24y+144= | | 8a+12b+4= | | 9x+12y+15= | | 6a-18b+12c= | | 12a-28b+10c= |